A discrete choice experiment to explore carer preferences. (13th March 2017) - Chester, Helen; Clarkson, Paul; Davies, Linda; Sutcliffe, Caroline; Roe, Brenda; Hughes, Jane; Challis, David
Abstract : Purpose: The purpose of this paper is to describe a case study to test the applicability of the discrete choice experiment (DCE) method to assess the preferences of carers of people with dementia. The focus of enquiry was home care provision. Design/methodology/approach: A multi-method approach was adopted for this pilot study. A literature review identified key characteristics of home care for dementia. This informed consultations with lay representatives. Key attributes of home care for the DCE were identified and formed the basis for the schedule. In all, 28 carers were recruited by two voluntary organisations to complete the DCE. A multinomial logistic regression model was used to analyse the data. Findings: Seven attributes of home care for people with dementia were identified from the consultation. The use of the DCE approach permitted the identification of those most important to carers. Despite the modest sample, statistically significant findings were reported in relation to five of the attributes indicating their relevance. A lay involvement in the identification of attributes contributed to the ease of administration of the schedule and relevance of the findings. Originality/value: This study demonstrated the utility of a DCE to capture the preferences of carers of people with dementia and thereby gather information from carers to inform policy, practice and service development. Their involvement in the design of the schedule was critical to this process.